Diagnostic Performance of Serum (1,3) Î²-D Glucan to Detect Fungal Infection in Acute Leukemia Patients with Chemotherapy - Dian Ariani Wirastuti; B. Rina A Sidharta; Yuwono Hadi Suparto; Leli Saptawati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Chemotherapy is a predisposing factor for infection in patients with malignancy, while culture, as the gold standard, limits the diagnosis of fungal infections. (1,3) Î²-D glucans, the most abundant polysaccharide component of the fungal wall, are increased in patients with Invasive Fungal Infections (IFI). This research was an analytical observational study with a cross-sectional approach involving 60 acute leukemia patients who received chemotherapy with suspicion of fungal infection at the General Hospital of Dr. Moewardi, Surakarta, from September to October 2019. Fungal blood cultures andserum (1,3) Î²-D glucan levels by the enzyme-linked immunoassay method were examined. Diagnostic tests were performed to determine sensitivity, specificity, Positive Predict Value (PPV), Negative Predict Value (NPV), Positive Likehood Ratio (PLR), Negative Likehood Ratio (NLR), and the serum's accuracy value (1,3) Î²-D glucan levels to fungal culture. Most (88.3%) of patients were diagnosed with Acute Lymphocytic Leukemia (ALL), maintenance chemotherapy phase (51.3%), risk factors for neutropenia (50%), and intravenous (IV) line use (56.7%). Serum (1,3) Î²-D glucan levels in patients with positive fungal cultures (4) in blood samples had a median of 482.87 (476.13-640.56) pg/mL, while patients with negative fungal cultures (56) had a mean±SD 298,68±114,39 pg/mL. Diagnostic test with a cut-off of 471,717 pg/mL showed sensitivity of 100.0%, specificity of 96.4%, NPV of 100%, PLR of 28.00, and NLR of 0.00 with an Area Under Curve (AUC) value of 0.982 and Coefficient Interval (CI) 95% (0.950-1.014). The measurement of serum (1,3) Î²-D glucan at a cut-off value of 471,717 pg/mL showed good performance as a biomarker for diagnosing and screening IFIs.